PERBANDINGAN PENGATURAN HUKUM DALAM KUHP LAMA DAN BARU BAGI ANAK YANG MENJADI KORBAN PERDAGANGAN ORANG - Anugra Soraya; Sunardi Purwanda; Muhammad Taufik (Universitas Stikubank, 2023)
The crime of trafficking in persons (TPPO) is an extraordinary crime that must be eradicated together. Anyone can become a victim, be it men, women, even children. This study aims to find out the form of legal arrangements for children who are victims of the crime of trafficking in persons in the old Criminal Code (KUHP) and the new Criminal Code in Law Number 1 of 2023 concerning the Criminal Code. The type of research used in this research is normative legal research. The approach used in this paper is the statutory approach and the comparative approach. The results of the study show that in the latest Criminal Code there is a detailed explanation regarding the crime of trafficking in persons, which regulates corporations, regarding the act of recruiting, transporting, harboring, sending, transferring or receiving a person, through threats of violence, use of force, kidnapping, confinement , forgery, fraud, abuse of power or position of vulnerability, debt bondage, or giving payments or benefits, as well as the minimum and maximum penalties that have been categorized in Law Number 1 of 2023.